Developing an Interactive Mathematics Multimedia Learning Based on Ispring Presenter in Increasing Students’ Interest in Learning Mathematics - Anwar, M Saidun; Choirudin, Choirudin; Ningsih, Eka Fitria; Dewi, Triana; Maseleno, Andino (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
The purpose of this study is to develop a multimedia learning based on iSpring Presenter to increase students' interest in learning in mathematics. This study uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The data analysis technique used is descriptive quantitative. The results showed that the interactive mathematics multimedia learning based on iSpring Presenter has fulfilled the requirements to be considered feasible to be used in the learning process and is feasible to be used as learning support media to increase students' interest in learning through varied learning activities.